Social movements and popular education. Struggles at companies in Portugal after april 25 - Rui Canário (Universidade Federal de Santa Catarina, 2009)
Using as an empirical reference the workers strike movement in the first halfof 1974 in the industrial belt of Lisbon, before and immediately after the defeatof the facist dictatorship, on April 25,1974, this paper seeks to reveal the educational potential of this autonomous social movement. It discusses the relationship between collective lessons realized in the realm of processes that established social change and the role ofthe State in these processes. In a broad theoretical framework, it analyzes the concept of emancipatory education. A clarification of this concept is understood to be essential to overcome a current critical disarmament in face of thelogic of capital. The paper analyzes and deconstructs a vision of social conflictin the 20th century, reduced to a dichotomy between two camps: capitalism and state capitalism. It is based on the supposition that all social actions and relations are infused with an educational dimension, which is an expression of politics and power relations.